A critical investigation of conflict management : a case study of a Namibian institution - Uiras, Hilja (Rhodes University, Faculty of Education, Department of Education, 1999)
This study is a qualitative interpretative study of conflict management in a multicultural Namibian institution. The focus of the study is to understand how individual people in a particular organization perceive conflict, the possible sources of conflict as well as to explore the possible strategies of managing conflict. This is followed by an analysis of the general educational cultural and social characteristics of Namibia, which relate to the sources of conflict. I also make an attempt to have a deeper understanding of people from different cultural and educational backgrounds in viewing conflict and how these differences might be seen as major sources of conflict and how they deal with it - by using a case study approach. I interviewed 5 participants from different cultural backgrounds. The major research methodology I used in this study is in-depth interviews that allowed me to explore people's understanding of, attitudes to and views on conflict. I supplemented the interviews with participant observation, which allowed me to get first-hand information on how people interact socially and in meetings in order to explore possible sources and existence of conflict in meetings and how the staff dealt with it. Furthermore, I tried as much as possible to observe daily activities as an observer. People interviewed have different perceptions about conflict. Some use conflict to their advantage to arouse discussion and stimulate creative thinking. Some people find conflict to be a burden, something to be minimized. This avoidance leads to poor decisions and poor use of teams as a way to improve both decision making and acceptance of the decisions that are made. Cultural differences among staff and the process of reform emerge as the major sources of conflict. Whether a conflict will result in negative or positive consequences, or both, will depend to a large part on the strategy taken to resolve the conflict.
Keywords: Conflict management -- Namibia; Conflict management -- Study and teaching; Culture conflict; Social conflict; Conflict management -- Namibia -- Case studies; Conflict management -- Study and teaching -- Case studies; Culture conflict -- Namibia -- Case studies; Social conflict -- Namibia -- Case studies